Charts With Variable Sample Sizes and Sampling Intervals - Costa, Antonio F.B. (My University, 1995)
Recent theoretical studies have shown that the chart with variable sampling intervals (VSI) and the chart with variable sample sizes (VSS) are quicker than the traditional chart for detecting shifts in a process. This article considers the chart with variable sample sizes and sampling intervals (VSSI). It is assumed that the amount of time the process remains in control has an exponential distribution. The properties of the VSSI chart are obtained using Markov chains. The VSSI chart is shown to be quicker than the VSI or VSS charts in detecting moderate shifts in the process.